Studi Ketimpangan Akses Pelayanan Kesehatan Peserta BPJS di Pedesaan dan Perkotaan - Naser, Alhairina; Haniarti, Haniarti; Wahyuni Sari, Rasidah; Muin, Herlina; Nurlinda, Nurlinda (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
The disparity in access to health services between rural and urban areas is a challenge in the implementation of the National Health Insurance (JKN) program by BPJS Kesehatan. This study aims to determine the relationship between geographic, socioeconomic, and government policy factors on access to BPJS services in Curio District, Enrekang Regency. The study used a quantitative-descriptive approach with an accidental sampling technique on 88 respondents (44 rural and 44 urban). The results of the chi-square test showed that there was no significant relationship between geographic factors (p = 0.658) and government policies (p = 0.658) with access to BPJS services. However, there was a significant relationship between socioeconomic factors (education, occupation, income) and access to BPJS services (p = 0.03). The conclusion of this study is that inequality in access is more influenced by socioeconomic factors than geography and policies. Therefore, it is recommended that the government strengthen health literacy, build health infrastructure in rural areas, and increase the effectiveness of BPJS policy dissemination evenly. Efforts to equalize services need to be focused on strengthening economic capacity and educating the public to optimize the use of BPJS services in a fair manner